Investigating the synergistic effects of carbon fiber and silica fume on concrete strength and eco-efficiency - Ahsan Waqar; Muhammad Basit Khan; Muhammad Talal Afzal; Dorin Radu; Teofil Gălăţanu; Christiana Emilia Cazacu; Yakubu Dodo; Fadi Althoey; Hamad R. Almujibah (Elsevier - Case Studies in Construction Materials, 2024)
The present study endeavors to quantitatively evaluate the performance of concrete by incorporating carbon fiber reinforcement and micro silica addition. A comprehensive experimental investigation is conducted to examine the effects of these two additives on the concrete properties. Additionally, an eco-efficiency analysis is performed to assess the environmental impact of the modified concrete. Furthermore, a response surface optimization technique is employed to optimize the concrete mix design based on desired performance criteria. The findings of this study provide valuable insights into enhancing the performance and eco-efficiency of concrete by utilizing carbon fiber reinforcement and micro silica addition. To accomplish this objective, varying percentages of CF (ranging from 0% to 0.80%) and different densities of micro silica (ranging from 0 kg/m3 to 50 kg/m3) were incorporated into the concrete mixtures. Subsequent tests were conducted to evaluate the mechanical properties, including compressive strength, split tensile strength, and flexural strength, at least 3 specimens for each mix were tested. Furthermore, the eco-strength efficiency of the concrete mixtures was assessed by determining the ratios of embodied carbon. The results demonstrate that the inclusion of 0.60% CF and 26.5 kg/m3 of micro silica in the concrete mixture yields the optimal proportion, leading to a significant enhancement in compressive strength (CS), split tensile strength (STS), and flexural strength (FS) by 54.11%, 80%, and 36.6%, respectively, compared to a control sample devoid of CF and micro silica. Through thorough experimentation, a response surface methodology (RSM) was employed to develop an optimized model. Consequently, the derived equations enable the calculation of the impact of adding carbon fiber to concrete.
Keywords: Carbon fiber; Environmental assessment; Response surface methodology; Mechanical properties